1984
DOI: 10.1111/j.1365-2141.1984.tb06118.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and autografting for chronic granulocytic leukaemia in transformation: probable prolongation of survival for some patients

Abstract: Between June 1977 and July 1983 51 patients with Ph1-positive chronic granulocytic leukaemia (CGL) in transformation were treated either by chemotherapy or by chemoradiotherapy followed by autografting with haemopoietic stem cells collected from their peripheral blood at the time of diagnosis. Forty-eight patients were restored to a second chronic phase. The median duration of survival after autografting was 26 weeks (range 2-152 weeks). Twenty-one patients with relatively long durations of second chronic phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 12 publications
(11 reference statements)
0
27
0
1
Order By: Relevance
“…Cells collected with one or two aphereses at the time of diagnosis proved to be sufficient to restore hematopoiesis to chronic phase in patients with transformed chronic myeloid leukemia when they were given after high-dose chemotherapy and/or total body irradiation. 12,13 In vitro studies revealed that patients with lymphoma or solid tumors had high numbers of circulating stem cells as a rebound phenomenon after intensive chemotherapy. 14 Adequate numbers of stem cells could be collected for autologous transplantation during a well-defined time window.…”
mentioning
confidence: 99%
“…Cells collected with one or two aphereses at the time of diagnosis proved to be sufficient to restore hematopoiesis to chronic phase in patients with transformed chronic myeloid leukemia when they were given after high-dose chemotherapy and/or total body irradiation. 12,13 In vitro studies revealed that patients with lymphoma or solid tumors had high numbers of circulating stem cells as a rebound phenomenon after intensive chemotherapy. 14 Adequate numbers of stem cells could be collected for autologous transplantation during a well-defined time window.…”
mentioning
confidence: 99%
“…Such patients are almost always restored to 'second' CP [17, 181, but the duration of benefit is usually quite short. Although this approach cannot be regarded as standard practice for the management of CML in transformation, it was of great interest nevertheless to observe that some patients treated in this way achieved Ph-negative hemopoiesis and that this Ph-negativity could in some cases be maintained for some months [17]. Because of these early observations, it was not entirely unexpected that patients autografted in CP could also achieve Ph-negative hemopoiesis; this condition has been prolonged in a minority of cases [19].…”
Section: Results Of Autografting With Blood or Marrowmentioning
confidence: 99%
“…38 In addition, it has been shown that patients who do not respond cytogenetically to IFN␣, may revert to IFN␣ exactly evident from (n = 12)/ +G-CSF paper; 41% of (n = responsiveness after intensive chemotherapy and autoSCT. 39,40 All these studies suggest an additive effect of intensive chemotherapy to an already impressive antileukaemic activity of IFN␣ alone. A prospective randomised trial under the auspices of the EBMT addressing the question whether autoSCT followed by IFN␣ vs IFN␣ alone improves survival is currently being performed.…”
Section: Discussionmentioning
confidence: 99%